Commercially Available Mobile Phone Headache Diary Apps: A Systematic Review - Hundert, Amos S; Huguet, Anna; McGrath, Patrick J; Stinson, Jennifer N; Wheaton, Mike (JMIR Publications, 2014)
BackgroundHeadache diaries are often used by headache sufferers to self-monitor headaches. With advances in mobile technology, mobile electronic diary apps are becoming increasingly common. ObjectiveThis review aims to identify and evaluate all commercially available mobile headache diary apps for the two most popular mobile phone platforms, iOS and Android. MethodsThe authors developed a priori a set of 7 criteria that define an ideal headache diary app intended to help headache sufferers better understand and manage their headaches, while providing relevant data to health professionals. The app criteria were intended as minimum requirements for an acceptable headache diary app that could be prescribed by health care professionals. Each app was evaluated and scored against each criterion. ResultsOf the 38 apps identified, none of the apps met all 7 app criteria. The 3 highest scoring apps, meeting 5 of the app criteria, were iHeadache (developed by Better QOL), ecoHeadache (developed by ecoTouchMedia), and Headache Diary Pro (developed by Froggyware). Only 18% of the apps were created with scientific or clinical headache expertise and none of the apps reported on psychometric properties. ConclusionsDespite the growing market and demand, there is a concerning lack of scientific expertise and evidence base associated with headache diary apps.